KONSEP PENDIDIKAN ANAK DALAM SURAT LUQMAN - Kasmiati, Kasmiati (Pusat Studi Gender dan Anak, IAIN Palu, 2018)
Education in Luqman's letter is education that teaches problems of wisdom and gratitude. Then in the Luqman letter, it is also stated that the parents' responsibility for the child's education is defined by the obligation of the child to serve his parents. Next Luqman's direction to the nature of performing Prayers shows that prayer is a very important matter that becomes a link between His servant and God, and advises repentance to call for virtue and obey the prohibition (amar ma'ruf nahi mungkar). The concept of children's education in the Luqman Letter is Tawhid / Aqidah Education, Moral Education, Worship Education, and Social Education.